2014
DOI: 10.3945/ajcn.113.069369
|View full text |Cite
|
Sign up to set email alerts
|

Sugars and risk of mortality in the NIH-AARP Diet and Health Study

Abstract: In this large prospective study, total fructose intake was weakly positively associated with all-cause mortality in both women and men, whereas added sugar, sucrose, and added sucrose intakes were inversely associated with other-cause mortality in men. In our analyses, intake of added sugars was not associated with an increased risk of mortality. The NIH-AARP Diet and Health Study was registered at clinicaltrials.gov as NCT00340015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 77 publications
(78 reference statements)
2
87
3
1
Order By: Relevance
“…After a median of 14.6 years of follow-up, added sugar intake was associated with a 2-fold greater risk of CVD death comparing extreme quintiles of intake. In contrast, an analysis from the NIH-AARP Diet and Health Study; a prospective cohort of older US adults, found that intake of total fructose but not of added sugar was associated with a modest increase in risk of all-cause mortality in men and women (23). However, total sugars from beverages, including added sugar were positively associated with risk of all-cause, CVD and other-cause mortality in women while only fructose from beverages was positively associated with risk of all-cause and CVD mortality in men.…”
Section: Cardiovascular Riskmentioning
confidence: 99%
“…After a median of 14.6 years of follow-up, added sugar intake was associated with a 2-fold greater risk of CVD death comparing extreme quintiles of intake. In contrast, an analysis from the NIH-AARP Diet and Health Study; a prospective cohort of older US adults, found that intake of total fructose but not of added sugar was associated with a modest increase in risk of all-cause mortality in men and women (23). However, total sugars from beverages, including added sugar were positively associated with risk of all-cause, CVD and other-cause mortality in women while only fructose from beverages was positively associated with risk of all-cause and CVD mortality in men.…”
Section: Cardiovascular Riskmentioning
confidence: 99%
“…The associations between sugars consumption and cancer have long been studied, yet, are difficult to demonstrate in an epidemiologic context (1–3). One of the major limitations in nutritional epidemiologic analyses is unreliability of self-reported dietary data, which can lead to severely distorted disease association estimates and reduced statistical power to detect an association (4).…”
Section: Introductionmentioning
confidence: 99%
“…In a large prospective study sugars from beverages -specifically, added fructose from fructose-glucose corn syrup, but not sugars from solid foods -were positively associated with overall mortality but not with the risk of major cancers [84]. Sugar-sweetened beverages raise insulin and glucose levels, and its consumption is associated with obesity and diabetes [85], which have been found to be related to pancreatic cancer risk [86,87].…”
Section: High-calorie Foods and Beveragesmentioning
confidence: 99%